Labor fatigue in rural workers - Karla Nayalle de Souza Oliveira; Leilson Rocha Bezerra; Maria Augusta Rocha Bezerra; Kaline Nayanne de Souza Oliveira; Cristianne Teixeira Carneiro (Universidade Federal do Ceará, 2013)
This is a research to identify the existence of labor fatigue in rural workers in Bom Jesus-PI, Brazil. This is a descriptive-exploratory study carried out from April to June, 2011, with 47 workers. Data collection took place by applying an instrument for evaluation of fatigue called "Bipolar Questionnaire" and semi-structured interview script and form to characterization of the socio-demographic profile and working conditions. The questionnaire was tabulated, being compared by Chi-Square test with 95% of reliability. It was performed for differentiation and classification of answers analyzed and observation of behavior within groups, the analysis of the main components and groups. It was observed that fatigue is common in a rural environment, mainly in the form of intense fatigue, due to the exposure to unhealthy conditions for the worker. Although they do not directly identify its trigger factors and therefore, their preventive measures.